Psychosocial and Biological Factors Contributing to Body Weight Gain in Schizophrenia - Shae-Leigh C. Vella; Nagesh B. Pai (Online Journal of Health & Allied Sciences, 2011)
Overweight and obesity are frequently reported to be a significant issue in schizophrenia resulting in the inherent complications of these disorders. Body weight gain also commonly results from treatment with the most tolerable and efficacious pharmacological treatments, second-generation antipsychotics. However there are numerous other factors that contribute to increased body mass in individuals with schizophrenia prior to the initiation of treatment. With prior research indicating that individuals with schizophrenia have higher rates of overweight and obesity before treatment. Therefore this article provides a review of pertinent issues associated with body weight gain in schizophrenia in an attempt to delineate the impact of both the disease and treatment upon body weight gain. The results of the review indicate that body weight gain in schizophrenia occurs from both psychosocial and biological factors that are further compounded by antipsychotic treatment. The article concludes with recommendations for future research.